FROM KINGDOM TO EMPIRE. POLITICAL LEGITIMACY BUILDING STRATEGIES AT THE COURT OF ALFONSO THE MAGNANIMOUS. - DONNE, FULVIO DELLE (Imago Temporis. Medium Aevum, 2022)
Alfonso the Magnanimous (1394-1458) became king of southern Italy in 1443, celebrating a spectacular Triumph. At his court, he gathered around himself the most important intellectuals of the time, from various places, who completely reworked his political consensus building strategies, adapting them to the new ruler’s imperial image. The king’s legitimacy strategies followed multiple paths (possession of virtues and dynastic inheritance), on various levels (rational, traditional and charismatic). The result was the invention of ‘Monarchical Humanism’, a type of Humanism whose salient characteristics were innovative, alternative and totally opposed to, but certainly no less important than, those of the ‘Civil Humanism’ developing elsewhere.